Comparison of Swim-Up and Microfluidic Sperm Sorting Methods in Selection of Sperm for Intracytoplasmic Sperm Injection - Ješeta, Michal; Doubravská, Adéla; Antalíková, Jana; Mekiňová, Lenka; Franzová, Kateřina; Remundová, Kateřina; Hošek, Jan; Kempisty, Bartosz; Hudeček, Robert (International journal of molecular sciences, 2025)
The use of microfluidic sperm sorting (MFSS) systems in infertility treatment is increasing due to their practicality and ease of use. While often presented as highly effective, their efficacy in patients with varying sperm analysis results remains uncertain. In this study, we evaluated the effectiveness of MFSS compared with the swim-up (SU) technique in terms of oxygen radical levels and spermiogram parameters. Samples from each patient were processed using both methods, followed by assessments of sperm concentration, motility, morphology, DNA integrity, acrosomal status, and mitochondrial membrane potential. Participants were selected based on sperm analysis and categorized as normozoospermic (n = 40) or non-normozoospermic (n = 28). An analysis of separation techniques revealed no significant differences, except for a lower percentage of DNA-fragmented sperm in the MFSS group compared with SU within the non-normozoospermic cohort (SU: 10.0% vs. MFSS: 5.69%, p = 0.027). No differences were observed between SU and MFSS in normozoospermic men. The MFSS method is a simple technique, frequently used in laboratories, that yields good results but does not offer a substantial advantage over SU. The primary benefit of MFSS appears to be a significant reduction in the proportion of sperm with DNA fragmentation compared with SU in patients with abnormal sperm analysis results.
Keywords: mikrofluidika; Male; Semen Analysis; Sperm Motility; Infertility, Male; fragmentace DNA; separace buněk; Membrane Potential, Mitochondrial; Spermatozoa; Adult; dospělí; Sperm Injections, Intracytoplasmic; mužské pohlaví; sperm separation; DNA Fragmentation; lidé; Cell Separation; Humans; motilita spermií; intracytoplazmatické injekce spermie; sperm analysis; spermie; membránový potenciál mitochondrií; IVF/ICSI; Microfluidics; mužská infertilita; spermatozoa; infertility; analýza spermatu